ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK CAMPURAN DAN BANK ASING MENGGUNAKAN METODE RGEC PERIODE 2012 – 2015 - Widayaningsih, Fadjar Harimurti & Bambang Widarno (Universitas Slamet Riyadi, 2017)
The objective of research is to compare the performance of Mixed Bank andForeign Bank in the period of 2012-2015. This study employed a case study in ANZIndonesia and Citibank Indonesia banks using purposive sampling as the samplingtechnique. The data source employed was secondary data obtained indirectly fromthe company through library study. Technique of analyzing data used was RGECratio analysis and independent sample t-test. The result of research were shown asfollows there was a difference of financial performance between ANZ Indonesia andCitibank Indonesia banks the period of 2012-2015. Citibank Indonesia had betterperformance than ANZ Indonesia did, viewed from GCG and NIM mean while, theresult of independent sample t-test on IRR, BOPO and ROA showed no difference ofperformance between ANZ Indonesia and Citibank Indonesia banks the period of2012-2015.Keywords: NPL, IRR, NPL, BOPO, GCG, ROA, NIM, CAR.